Professional communication - Guptā, Renu (University Science Press, an imprint of Laxmi Publications Pvt Ltd, 2021)
"To enable the students to- Cultivate and develop reading and writing habit to enhance their vocabulary.develop communication skills necessary for effective presentation and management.know various types of essays, letters, stories and journalistic writing."--